In out-of-hospital cardiac arrest, is the positioning of victims by bystanders adequate for CPR? A cohort study - Julia Braun; Patrick Wagner; Hans-Richard Arntz; Jan Breckwoldt; Sebastian Schloesser (BMJ Open)
Objectives Outcome from out-of-hospital cardiac arrest (OHCA) highly depends on bystander cardiopulmonary resuscitation (CPR) with high-quality chest compressions (CCs). Precondition is a supine position of the victim on a firm surface. Until now, no study has systematically analysed whether bystanders of OHCA apply appropriate positions to victims and whether the position is associated with a particular outcome.Design Prospective observational cohort study.Setting Metropolitan emergency medical services (EMS) serving a population of 400 000; dispatcher-assisted CPR was implemented. We obtained information from the first EMS vehicle arriving on scene and matched this with data from semi-structured interviews with witnesses of the arrest.Participants Bystanders of all OHCAs occurring during a 12-month period (July 2006–July 2007). From 201 eligible missions, 200 missions were fully reported by EMS. Data from 138 bystander interviews were included.Primary and secondary outcome measures Proportion of positions suitable for effective CCs; related survival with favourable neurological outcome at 3 months.Results Positioning of victims at EMS arrival was ‘supine on firm surface’ in 64 cases (32.0%), ‘recovery position (RP)’ in 37 cases (18.5%) and other positions unsuitable for CCs in 99 cases (49.5%). Survival with favourable outcome at 3 months was 17.2% when ‘supine position’ had been applied, 13.5% with ‘RP’ and 6.1% with ‘other positions unsuitable for CCs’; a statistically significant association could not be shown (p=0.740, Fisher’s exact test). However, after ‘effective CCs’ favourable outcome at 3 months was 32.0% compared with 5.3% if no actions were taken. The OR was 5.87 (p=0.02).Conclusion In OHCA, two-thirds of all victims were found in positions not suitable for effective CCs. This was associated with inferior outcomes. A substantial proportion of the victims was placed in RP. More attention should be paid to the correct positioning of victims in OHCA. This applies to CPR training for laypersons and dispatcher-assisted CPR.